2021
DOI: 10.3390/mi12020189
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Edge Mode on Mass Sensing for Strained Graphene Resonators

Abstract: Edge mode could disturb the ultra-subtle mass detection for graphene resonators. Herein, classical molecular dynamics simulations are performed to investigate the effect of edge mode on mass sensing for a doubly clamped strained graphene resonator. Compared with the fundamental mode, the localized vibration of edge mode shows a lower frequency with a constant frequency gap of 32.6 GHz, despite the mutable inner stress ranging from 10 to 50 GPa. Furthermore, the resonant frequency of edge mode is found to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…The different responses of the local and the basic modes to adsorption mass, and the effects of the local modes on the quality factor of mechanical vibration were examined. The results show that increasing the aspect ratio and pre-stressing of graphene sheets can effectively improve the quality factor of the graphene resonant mass sensor [92].…”
Section: Graphene Resonant Mass Sensormentioning
confidence: 95%
“…The different responses of the local and the basic modes to adsorption mass, and the effects of the local modes on the quality factor of mechanical vibration were examined. The results show that increasing the aspect ratio and pre-stressing of graphene sheets can effectively improve the quality factor of the graphene resonant mass sensor [92].…”
Section: Graphene Resonant Mass Sensormentioning
confidence: 95%
“…Simulation in the canonical NVT ensemble at the same temperature (where atomic number, volume, and temperature are kept constant). The edges of the graphene were fixed after structural relaxation and a sinusoidal velocity excitation as shown in equation (2) [10,12,42] was applied to the central part.…”
Section: Modeling and Methodsmentioning
confidence: 99%
“…With the hybrid structure of graphene supported by carbon nanotubes (CNTs) being employed in resonators and proven feasible, the origami graphene structure could also be a strong candidate for resonators. Xiao et al [12] proposed a mass determination method using the first three resonance modes to avoid interference of stress fluctuations in graphene. Ye et al [13] reported on the first experimental demonstration of electrothermally tuned single-and few-layer graphene NEMS resonators operating in the high-frequency (HF) and very highfrequency bands and demonstrated a wide tuning frequency range of up to D = / f f 310%.…”
Section: Introductionmentioning
confidence: 99%
“…[259] These measurements of resonant frequency due to attached light mass can be combined with the optical and electrical measurement methods demonstrated in Section 3 so as to further enhance the measuring efficiency. Other theoretical calculations of 2D material based mass sensors have studied the influence of temperature, [260] in-plane magnetic field, [261] layer numbers, [262] internal stress, [263] diameter to thickness ratio [264] and higher order nonlinear vibration modes. [265] The results of these theoretical calculations provide feasible suggestions for future experiments with enhanced sensitivity and reliability of mass sensors.…”
Section: Mass and Pressure Sensors Based On Suspended 2d Materials Re...mentioning
confidence: 99%